Coping Behavior Al-Ghazali pada Mahasiswa Psikologi - Nur Aziz Afandi (Universitas Islam Tribakti Lirboyo Kediri, 2017)
Imam al-Ghazali as hujjatul al-islam has formulated a conceptual coping behavior in tazkiyah al-nafs which derives from his work ihya 'ulum al-diin. The purpose of this study is to find out how the form of coping behavior of Al-Ghazali ozn psychology students of semester VII is one of Islamic universities in Malang. This type of research is descriptive. The population of this study is all students of psychology semester VII force 2001-2002 one of the Islamic universities in Malang which amounted to 80 people, and for a reason of the absence of subject when filling in questionnaire, the subject of research there are 76 people. The result of the research using questionnaire coping behavior of Al-Ghazali as its instrument shows that there are 4 subjects (5,3%) from 76 subjects who have kafah coping behavior or implement all aspects of Al-Ghazali coping behavior, while subjects who have non-kafah coping behavior or not Implementing some of the aspects of coping behavior is as much as 72 subjects (94,7). The coping behavior aspect group employed by all study subjects was sequential as follows: rub 'al-munjiyat (81.3%) followed by rub' al-muhlikat (73.9%), rub 'al-adat (69.1% ) and rub 'al-ibadat (67.2%).